The Artificial Satellites’ Observation Using the Complex of Telescopes of RI «MAO» - Sybiryakova, Ye.S.; Shulga, O.V.; Vovk, V.S.; Kaliuzhniy, M.P.; Bushuev, F.I.; Kulichenko, M.O.; Haloley, M.I.; Chernozub, V.M. (Science and Innovation, 2024)
Special methods, means and software for cosmic objects’ observation and processing of obtained results were developed. Combined method, which consists in separated accumulation of images of reference stars and artificial objects, is the main method used in observations of artificial cosmic objects. It is used for observations of artificial objects at all types of orbits.